2022
DOI: 10.1002/casp.2627
|View full text |Cite
|
Sign up to set email alerts
|

Stop looking at me! associations between men's partner‐objectification and women's self‐objectification, body shame and life satisfaction in romantic relationships

Abstract: A growing amount of empirical evidence shows that sexual objectification can be elicited within the context of romantic relationships, leading to adverse consequences for women's well-being. However, most of this research assessed women's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Regarding self-objectification, it emerged that negative self-perceptions in women mediated the relationship between men’s partner-sexual objectification and their attitudes toward dating violence. Specifically, in line with the existing literature (Pecini et al, 2022; Strelan & Pagoudis, 2018), we found that men’s partner-sexual objectification and women’s self-objectification correlated. Furthermore, self-objectification emerged as the underlying mechanism explaining the relationship between being sexually objectified by the romantic partner and acceptance of dating violence in women.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Regarding self-objectification, it emerged that negative self-perceptions in women mediated the relationship between men’s partner-sexual objectification and their attitudes toward dating violence. Specifically, in line with the existing literature (Pecini et al, 2022; Strelan & Pagoudis, 2018), we found that men’s partner-sexual objectification and women’s self-objectification correlated. Furthermore, self-objectification emerged as the underlying mechanism explaining the relationship between being sexually objectified by the romantic partner and acceptance of dating violence in women.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, in our research, we investigated whether self-objectification in women would be positively associated with their attitudes toward dating violence (Hypothesis 3a). Furthermore, self-objectification is the primary consequence of objectifying experiences even in the context of romantic relationships (Pecini et al, 2022; Ramsey & Hoyt, 2015; Strelan & Pagoudis, 2018; but see Mahar et al, 2020) and represents the key mechanism linking experiences of sexual objectification to negative outcomes (Fredrickson & Roberts, 1997). Thus, we tested whether self-objectification mediated the link between men’s partner-sexual objectification and women’s attitudes toward dating violence (Hypothesis 3b).…”
Section: The Female Targets Perspective: Self-objectification and Att...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rudman and Mescher (2012) demonstrated that men who implicitly dehumanize women (as animals and objects) are also likely to rape and sexually harass them. Additionally, several studies (Bevens & Loughnan, 2019; Morera et al, 2022; Pecini et al, 2023) confirmed that dehumanization is associated with abuse in romantic relationships, greater dating violence, and more sexual aggression towards women.…”
Section: Biologization and Indirect Aggressionmentioning
confidence: 97%
“…The editorial team welcomes research from all areas of community and social psychology. We accept empirical, theoretical, and methodological articles, and welcome a wide range of methodologies, including quantitative (Pecini et al, 2022), qualitative (Varma & Siromahov, 2023), and mixed methods research (Kothari, Fischer, Mullican, Lipscomb, & Jaramillo, 2022), as well as correlational (Gray, Randell, Manning, & Cleveland, 2023), longitudinal (Joshanloo, 2022), and experimental designs (Mäkinen et al, 2022). Relatedly, we have expanded the types of articles that we accept.…”
mentioning
confidence: 99%